A Novel SDHA-deficient Renal Cell Carcinoma Revealed by Comprehensive Genomic Profiling. (June 2015) - Yakirevich, Evgeny; Ali, Siraj M.; Mega, Anthony; McMahon, Caitlin; Brodsky, Alexander S.; Ross, Jeffrey S.; Allen, Justin; Elvin, Julia A.; Safran, Howard; Resnick, Murray B.
Abstract : Succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) is an emerging provisional entity included in the 2013 International Society of Urological Pathology Vancouver Classification. Most genomic alterations in patients with SDH-deficient RCCs involve the SDHB subunit, and the associated renal tumors have loss of immunohistochemical SDHB expression and distinctive morphologic features. Renal tumors less commonly possess genomic alterations involving the SDHC and SDHD subunits, but no SDHA alterations have as yet been described. Here we identified a novel SDHA homozygous deletion in an aggressive variant of RCC diagnosed initially as unclassified type in a 54-year-old patient. A search for novel actionable mutations by comprehensive genomic profiling based on clinical next-generation sequencing evaluating entire coding regions of 315 cancer-related genes, including all SDH subunits, was performed. Sequencing identified a novel 17 kbp homozygous deletion of 9 SDHA exons on chromosome 5p15. SDHA and SDHB immunohistochemistry further confirmed that the homozygous deletion led to the loss of SDHA and SDHB protein expression. Histologically, the tumor had a mixed pattern of high-grade papillary and collecting duct carcinoma and distinctive pale eosinophilic cytoplasmic inclusions similar to those described in SDHB-deficient RCC. This is the first report that identifies SDHA inactivation in RCC. Additional studies utilizing comprehensive genomic profiling, immunohistochemistry, and careful morphologic evaluation are needed both prospectively and retrospectively to identify the group of RCCs harboring SDHA genomic alterations.